Model Komunikasi Penanganan Stunting Dan Modal Sosial Pada Masa Pandemi COVID-19 Di Indramayu - Hadi Purwanto; Purbudi Wahyuni; Susilastuti Dwi Nugrahajati; Eko Teguh Paripurno; Johan Danu Prasetya (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
During the Covid-19 Pandemic, there was a notable increase in the proportion of children experiencing stunted in Indramayu District. The lack of existing research on the linear communication model in relation to stunting and the promotion of social capital during the Covid-19 pandemic is a notable requires attention. This study is to conduct a qualitative study to examine the communication models of stunting and social capital within the specific setting of the Covid-19 Pandemic in Indramayu. This is influenced by the linear communication model and the limited choices for engagement in improving and utilizing social capital. The communication strategy shows ineffective communication and coordination, both within the government and between officials and parents or caregivers of undernourished young children, as well as inadequate utilization of GESIT application data. Therefore, it is crucial to develop an intervention strategy that includes legal components, models and communication methods. A communication model needs to be developed to provide a two-way communication, encourage input from caregivers, convergence of stakeholders, and provide training in communication techniques for the staff involved. To sustain the foster parent program, it is essential to enable communication and ensure two-way access for all parties involved.